Unintentional investigations: Truth in drama and "all that 'ordinary' in the phrase 'ordinary language philosophy' means". Issue 3 (2nd April 2022) - Forsberg, Niklas
This paper explores the notion of truth in relation to literature. It opens with a critical exposition of some dominant tendencies in contemporary aesthetics, in which narrow views of truth and reference guide the aesthetic investigations in harmful ways. One of the problems with such as view is not merely that it becomes difficult to talk about truth in art, but that it also makes the idea that we can learn something from literature problematic. The effort of this paper is thus to open up for a variety of notions of truth, that are not immediately tied to the notion of representation or correspondence. We need a way of talking about truth in art. The effort to explore a notion of truth in art that is not tied to narrow views about reference, and which broadens our sense of "aboutness" goes, in this paper, via a reading of Harold Pinter's Nobel Lecture from 2005, together with some reflections inspired by some of Stanely Cavell's reflections about the relevance of reflecting upon ordinary language. It is argued that literature engages in a form of conceptual reflection, by means of making the sense of our concepts clear and by challenging philosophical preconceptions about what our concepts must mean. What we can learn from art is thus not necessarily toed to either representation or authorial intent, but comes into view by means of the literary exercises that often (but certainly not always) require a conceptual sensitivity; that is, by means of careful attention to what words mean and what follows from them in specific contexts of use.